Halal logistics service quality: conceptual model and empirical evidence. Issue 11 (5th November 2018) - Zailani, Suhaiza; Jafarzadeh, Shima; Iranmanesh, Mohammad; Nikbin, Davoud; Selim, Nur Izatul Irani
Abstract : Purpose: The purpose of this paper is to devise and test a model of halal logistic service quality. Design/methodology/approach: To develop the halal logistics service quality model, the relevant literature was reviewed and a qualitative study was carried out on halal logistics service providers and their customers. A survey of 253 halal food and beverage firms in Malaysia was conducted, and based on the results, a model was developed and tested empirically. Findings: Based on the literature review, interviews, pretest and empirical study, a valid and reliable measurement instrument for halal logistics service quality was developed. Practical implications: The findings can help managers of halal logistics service providers to understand the criteria that halal food and beverage firms are considered to judge the quality of halal logistics services. Originality/value: This study makes a valuable contribution by proposing a halal logistics service quality model.